Spatial Interpolation of the Frequential Distribution of Thunderstorm and Rainfall over Balochistan, Pakistan - Sadiq, N.; Naz, H. (The Nucleus, 2014)
Tailored digital database of the Thunderstorm (TS) and Rainfall (RF) activities have been developed to analyze and quantify their distributional impacts through suitable spatial interpolation method (i.e. Inverse Distance to a Power) over the Balochistan province of Pakistan for the period of 1961-2010. The study also incorporates the annual and seasonal analyses. Annual percentage divulge the dominance of TS over RF from April to October while the contrariwise condition is observed for rest of the year. In seasonal analysis it is revealed that in winter the rainfall activity is markedly greater than the thunders while in premonsoon and monsoon the situation is vice versa; post-monsoon unveil the comparable frequencies. The extreme activity of TS and RF is found in June (≈45%) and March (≈46%), respectively. Akin patterns have been found for the both activities in winter and monsoon while postmonsoon season also alike. Winter rainfall is most active in the western parts of the province with largest value at Nokkundi (≈ 70%) while north eastern parts acquire least RF activity in post-monsoon particularly Zhob and Kalat (i.e. ≈ 2%).